NEW APPROACHES TO INDIVIDUALIZED CHOICE OF ORAL ANTICOAGULANTS IN PATIENTS WITH ATRIAL FIBRILLATION - Ju. P. Skirdenko; N. A. Nikolayev (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate adherence to treatment, mutations of the hemostatic system and food preferences as predictors of choice of optimal anticoagulant therapy in patients with atrial fibrillation (AF).Material and methods. 142 patients with AF were quantitatively evaluated in terms of their adherence to treatment, polymorphism of genes CYP2C9 and VKORC1 and the structure of food preferences.Results. Persons with insufficient adherence to treatment prevailed among AF patients, at that the leading negative factor was the low adherence to medical support, which directly related with the frequency of complications and ineffectiveness of anticoagulant therapy. The very high prevalence of gene mutations CYP2C9 and VKORC1 (more than 2.3 per 1 respondent) was detected in the study sample, which makes screening pharmacogenetic testing ineffective and is an independent risk factor for the Omsk region. Consumption by the population of food products that can affect anticoagulant therapy with warfarin does not have special regional characteristics and does not differ significantly among respondents both without AF and with AF (99.2±41.9 vs 100.8±38.6 points; р=0.82) as well as among patients with AF both taking and not taking warfarin (85.4±47.0 vs 107.3±42.1 points, p=0.9).Conclusion. Individualized choice of anticoagulant in patients with AF should be based on a structured quantitative assessment of adherence to treatment. In low adherence to treatment and choice of warfarin as an anticoagulant, its safety should be confirmed by the assessment of pharmacogenetic status and/or dietary preferences of the patient.